Compacting CNT sponge to achieve larger electromagnetic interference shielding performance. (15th April 2018) - Mei, Hui; Zhao, Xing; Xia, Junchao; Wei, Fei; Han, Daoyang; Xiao, Shanshan; Cheng, Laifei
Abstract: The present study reports a simple route for the synthesis of 3D carbon nanotube (CNT) sponges by vacuum assisted filtration of CNT bundles of variable compaction ratios and its epoxy (EP) composites with superior electromagnetic interference (EMI) shielding performance. The electrical and mechanical properties of CNT sponge/EP composites were investigated and findings enabled identification of a sponge compaction ratio of 70% as optimum for the improvement of the electrical conductivity and EMI shielding effectiveness of the material, by 138 and 41%, respectively, compared to uncompacted samples. Mechanical properties of the composites were also enhanced with the yield strength and elastic modulus of the composite of a compaction ratio of 70% improved by 17 and 25%, respectively compared to pure epoxy. These results indicate that CNT sponge with a higher compaction ratio is a potential filler for mechanically strong and high-performance EMI shielding nanocomposites. Graphical abstract: Highlights: Micro-scale CNT bundles were utilized to build 3D CNT sponges of different compaction ratios. Conductivity and EMI-SE of epoxy composite were dramatically increased with compaction ratio. Epoxy composite with high compaction ratio shows good compressive performance.